Carbon Dioxide Level between Nasal High-Frequency Oscillatory Ventilation and Synchronized Nasal Intermittent Positive Pressure Ventilation after Extubation in Neonates: A Cross-over Randomized Controlled Trial - Baingam, Kulthida; Phatigomet, Manapat; Thatrimontrichai, Anucha; Maneenil, Gunlawadee; Dissaneevate, Supaporn; Janjindamai, Waricha (American Journal of Perinatology, 2023)
Objective Nasal high-frequency oscillatory ventilation (nHFOV) and synchronized nasal intermittent positive pressure ventilation (sNIPPV) yield a lower partial pressure of carbon dioxide (pCO2) after extubation than nasal continuous positive airway pressure. Our aim was to clarify which of the two was superior.Study Design We performed a crossover randomized study to evaluate pCO2 level among 102 participants from July 2020 to June 2022. Intubated preterm and term neonates with arterial lines were randomly allocated to nHFOV–sNIPPV or sNIPPV–nHFOV sequences; their pCO2 levels were measured after 2 hours in each mode. Subgroup analyses were performed for preterm (gestational age <37 weeks) and very preterm (gestational age <32 weeks) neonates.Results The mean gestational age (nHFOV–sNIPPV, 32.8 vs. sNIPPV–nHFOV, 33.5 weeks) and median birth weight (1,850 vs. 1,930 g) did not differ between the sequences. The mean ± standard deviation pCO2 level after nHFOV (38.7 ± 8.8 mm Hg) was significantly higher than that after sNIPPV (36.8 ± 10.2 mm Hg; mean difference: 1.9 mm Hg; 95% confidence interval: 0.3–3.4 mm Hg; treatment effect [p = 0.007] but no sequence [p = 0.92], period [p = 0.53], or carryover [p = 0.94] effects). However, the difference in pCO2 level between the sequences was not statistically significant in the subgroup analyses of preterm and very preterm neonates.Conclusion After neonatal extubation, the sNIPPV mode was associated with a lower pCO2 level than the nHFOV mode with no significant difference in preterm and very preterm neonates.Key Points
Keywords: airway extubation; carbon dioxide; high-frequency ventilation; intermittent positive pressure ventilation; newborn; noninvasive ventilation